Comparison of external jugular venous access with internal jugular venous access in pediatric shock: An observational, prospective study - Amit Kumar (Journal of Pediatric Critical Care, 2021)
Background: Central venous access is usually preferred over the peripheral venous route when circulatory failure needs inotropes and vasopressors. However, in resource-limited settings with underskilled personnel, it is not feasible always and so patients are being treated with the peripheral venous route with variable results. We aimed to compare external jugular venous (EJV) access with internal jugular venous (IJV) access for effectiveness, ease of procedure, complications, and treatment cost in pediatric shock. Subjects and Methods: This was a prospective, nonrandomized, observational study from January 2014 to June 2015 in 66 pediatric patients with shock at a 7-bedded pediatric intensive care unit. Parents were explained about both routes. Depending on their affordability and consent, one route was chosen. Pertinent data were obtained, and analysis was done as per objectives. Results: EJV and IJV had 50 and 16 patients, respectively. Baseline characteristics were comparable. Death and discharge against medical advice rates are high in both the groups. No procedure-related life-threatening complications in any group and local site problems were similar in both the groups. Overall attempts and duration of procedure were similar in both the groups, and although the initial cost of the procedure of the IJV group was higher, overall final hospital bill had no significant difference. The median (Q1, Q3) hours of achieving shock-free status were 48 (24, 96) and 46 (12, 108) (P = 0.412). The median (Q1, Q3) improvement in base deficit at the end of 24 h was −4.5 (−8.1, 0.27) and −1.9 (−4.2, −0.6) (P = 0.259) in the EJV and IJV groups, respectively. Conclusion: For pediatric shock management, EJV access is an effective, easy, and cost economic procedure without significant complications as compared to IJV access.